Catalytic Dynamic Kinetic Resolutions in Tandem to Construct Two-Axis Terphenyl Atropisomers - Beleh, Omar M. (J Am Chem Soc, 2020)
The defined structure of molecules bearing multiple stereogenic axes is of increasing relevance to materials science, pharmaceuticals, and catalysis. However, catalytic enantioselective approaches to control multiple stereogenic axes remain synthetically challenging. We report the catalytic synthesis of two-axis terphenyl atropisomers, with complementary strategies to both chlorinated and brominated variants, formed with high diastereo- and enantioselectivity. The chemistry proceeds through a sequence of two distinct dynamic kinetic resolutions: first, an atroposelective ring-opening of Bringmann-type lactones produces a product with one established axis of chirality; second, a stereoselective arene halogenation delivers the product with the second axis of chirality established. In order to achieve these results, a class of Brønsted basic guanidinylated peptides, which catalyze an efficient atroposelective chlorination, is reported for the first time. In addition, a complementary bromination is reported, which also establishes the second stereogenic axis. These bromo-terphenyls are accessible following the discovery that chiral anion phase transfer catalysis by C(2)-symmetric phosphoric acids allows catalyst control in the second stereochemistry-determining event. Accordingly, we established the fully catalyst-controlled stereodivergent synthesis of all possible chlorinated stereoisomers, while also demonstrating diastereodivergence in the brominated variants, with significant levels of enantioselectivity in both cases.